ANALISIS STRATEGI PENINGKATAN RETRIBUSI TEMPAT REKREASI DAN OLAHRAGA PADA OBYEK WISATA ALAM SIDAN KABUPATEN GIANYAR - Laksmi Githa, Putu Diah; Supriliyani, Ni Wayan; Yudartha, I Putu Dharmanu (CITIZEN CHARTER, 2018)
ABSTRACT The purpose of this research was to identify the extent of the implementation of the strategy undertaken as well as efforts to design the strategy on the next program. The unit of analysis of this research was Tourism Office of Gianyar Regency and this research used descriptive qualitative method. The results of this study indicate that in the implementation of the strategy applied by the Tourism Office of Gianyar Regency in increasing recreation and sports retribution still experienced some obstacles, both in strategic planning and implementation in the field. This research produces alternative strategy of SO (Strengths-Opportunities) that is, develop tourist attraction owned, improve the utilization of IT as a means of providing tourist information, develop new tourism innovation, the development of local community industry in the path of tourism, environmental arrangement along the access of tourism, developing new marketing innovations, as well as improving the facilities and infrastructure of tourism objects. Keywords: Strategy, Recreation and Sports Retribution, Alam Sidan